Mother-Child Reports of Affectionate Communication with Fathers: Associations with Family Satisfaction and Life Satisfaction. (1st September 2016) - Curran, Timothy M.; Yoshimura, Stephen M.
Abstract : This study examined the possibility that mothers' and children's perceptions of affection with the children's father spill over to perceptions of affectionate communication in related family subsystems, and affect individual levels of family and life satisfaction. Using the Actor-Partner Interdependence Model (APIM), we tested these relationships with 75 mother-child dyads reporting on perceptions of affection with fathers. The results show that both mothers and children perceived the family subsystem outside of their direct experience as more affectionate when they reported higher levels of affectionate communication with the father. In addition, affectionate communication with the father was linked to both family and life satisfaction for mothers and children. Implications for understanding spillover of affection in families are discussed.